Molecular mechanism of K65 acetylation-induced attenuation of Ubc9 and the NDSM interaction - Naik, Mandar T. (Sci Rep, 2017)
The negatively charged amino acid-dependent sumoylation motif (NDSM) carries an additional stretch of acidic residues downstream of the consensus Ψ-K-x-E/D sumoylation motif. We have previously shown that acetylation of the SUMO E2 conjugase enzyme, Ubc9, at K65 downregulates its binding to the NDSM and renders a selective decrease in sumoylation of substrates with the NDSM motif. Here, we provide detailed structural, thermodynamic, and kinetics results of the interactions between Ubc9 and its K65 acetylated variant (Ac-Ubc9(K65)) with three NDSMs derived from Elk1, CBP, and Calpain2 to rationalize the mechanism beneath this reduced binding. Our nuclear magnetic resonance (NMR) data rule out a direct interaction between the NDSM and the K65 residue of Ubc9. Similarly, we found that NDSM binding was entropy-driven and unlikely to be affected by the negative charge by K65 acetylation. Moreover our NMR, mutagenesis and molecular dynamics simulation studies defined the sequence of the NDSM as Ψ-K-x-E/D-x(1)-x(2)-(x(3)/E/D)-(x(4)/E/D)-x(n) and determined that K74 and K76 were critical Ubc9 residues interacting with the negatively charged residues of the NDSM.